Care providers' perceptions towards challenges and opportunities for service improvement at diabetes management clinics in public primary health care in Muscat, Oman: a qualitative study - Kamila Al-Alawi; Ahmed Al Mandhari; Helene Johansson (BMC, 2019)
Abstract Background The literature has described several challenges related to the quality of diabetes management clinics in public primary health care centres in Oman. These clinics continue to face challenges due to the continuous growth of individuals diagnosed with type 2 diabetes. We sought to explore the challenges faced in these clinics and discuss opportunities for improvement in Oman. Methods This qualitative study was designed to include non-participant observations of diabetic patients and care providers during service provision at diabetes management clinics, as well as semi-structured interviews with care providers, at five purposively selected public primary health care centres. Care providers included physicians, nurses, dieticians, health educators, pharmacists, an assistant pharmacist, a psychologist, and a medical orderly. The data were analysed using qualitative content analysis. Results The study disclosed three different models of service delivery at diabetes management clinics, which, to varying degrees, face challenges related to health centre infrastructure, technical and pharmaceutical support, and care providers' interests, knowledge, and skills. Challenges related to the community were also found in terms of cultural beliefs, traditions, health awareness, and public transportation. Conclusion The challenges encountered in diabetes management clinics fall within two contexts: health care centres and community. Although many challenges exist, opportunities for improvement are available. However, improvements in the quality of diabetic clinics in primary health care centres might take time and require extensive involvement, shared responsibilities, and implications from the government, health care centres, and community.